COW FARMER SATISFACTION WITH INSEMINATOR SERVICE IN THE VILLAGE OF BUAHAN PAYANGAN DISTRICTS GIANYAR REGENCY IN BALI - I P., Purnawiasa; Sukanata, I W.; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This research was conducted in the Village, Payangan District, Gianyar Regency which took place from September to November 2020. The purpose of this study was to determine the attributes that need to be maintained and improved, namely service quality based on service dimensions such as physical evidence, responsiveness, assurance and empathy. The data used is primary data collected through interviews with 60 cow breeders who have carried out IB (aeftor IB) at least 3 times which were selected randomly. The data obtained were analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results showed that the overall service quality level of farmers' satisfaction with the service quality of the inseminator in Buahan village was classified as satisfied with a CSI value of 77%. Meanwhile, separately, breeders are satisfied with the dimensions of physical evidence service, responsiveness, empathy with the CSI value of each CSItangible of 76.4%, the value of CSI responsiveness of 74.6%, the value of CSI Empathy of 76.2%, the value of CSIreriability of 81, 6% and CSIassurance 80.8%. The CSI value that has not been maximized must be considered by the inseminator to be improved so that farmer satisfaction is maximized. The service attributes that need to be maintained or improved to increase maximum farmer satisfaction are: injecting mating equipment, quality of the resulting offspring, service procedures, IB officers, IB officer expertise, guarantees, guarantees. Keywords: CSI, IPA, Cow